2016
DOI: 10.1093/brain/aww237
|View full text |Cite
|
Sign up to set email alerts
|

Exosome secretion is a key pathway for clearance of pathological TDP-43

Abstract: Cytoplasmic TDP-43 aggregation is a pathological hallmark of amyotrophic lateral sclerosis and frontotemporal lobar degeneration. Here we investigated the role of exosomes in the secretion and propagation of TDP-43 aggregates. TDP-43 was detected in secreted exosomes from Neuro2a cells and primary neurons but not from astrocytes or microglia. Evidence is presented that protein aggregation and autophagy inhibition are factors that promote exosomal secretion of TDP-43. We also report that levels of exosomal TDP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
237
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(250 citation statements)
references
References 56 publications
11
237
2
Order By: Relevance
“…TDP-35 participates in the aggregation of mRNA precursors, which makes the transformation of proteins into polymers easier. The insoluble fraction of ALS acts as a seed of TDP-43 aggregation when it is introduced in SH-SY5Y cells, and subsequently transmitted to other co-cultured cells [19,29] . Such extracellular accumulation, in a potentially more harmful way, is similar to the prion infections [30,31] .…”
Section: Redistribution Of Intracellular Tdp-43mentioning
confidence: 99%
See 2 more Smart Citations
“…TDP-35 participates in the aggregation of mRNA precursors, which makes the transformation of proteins into polymers easier. The insoluble fraction of ALS acts as a seed of TDP-43 aggregation when it is introduced in SH-SY5Y cells, and subsequently transmitted to other co-cultured cells [19,29] . Such extracellular accumulation, in a potentially more harmful way, is similar to the prion infections [30,31] .…”
Section: Redistribution Of Intracellular Tdp-43mentioning
confidence: 99%
“…The pathological TDP-43 protein aggregation and autophagy inhibition promote exosomal secretion of TDP-43 [29] . The levels of exosomal full length TDP-43 and C-terminal fragment species are upregulated in the brain of ALS patients.…”
Section: The Spreading Of Pathological Tdp-43mentioning
confidence: 99%
See 1 more Smart Citation
“…TDP-43 oligomers or aggregates also transmit from donor to recipient cells in culture, either through tunneling nanotubes or exosomes 86-89 . Cell culture experiments suggest that the ceramide-dependent exosomal pathway is involved in exosomal TDP-43 release 88 . As TDP-43 is also present in exosomal fractions from brains and CSF of healthy controls, its assembly into disease-associated aggregates might not cause the sorting into EVs 87,89 .…”
Section: Evidence For Secretion Of Human Proteins With Prlds In Assocmentioning
confidence: 99%
“…Recent studies have shown that they can transfer insoluble aggregates to neighboring cells, resulting in a decreased toxic load on the proteome: whether the spreading of protein aggregates via exosomes could provide the molecular basis for the prion-like mechanism of disease propagation in neurodegeneration is certainly very intriguing (Yuyama et al, 2012; Schneider and Simons, 2013; Iguchi et al, 2016) and has the potential to be exploited for therapeutic and biomarker discovery (Boukouris and Mathivanan, 2015; Yuyama et al, 2015). …”
Section: The Proteostasis Networkmentioning
confidence: 99%